Minimally invasive mitral valve replacement redo surgery under ventricular fibrillation in a patient with dextrocardia and situs inversus totalis: a case report - Yu Han; Junnan Zheng; Pranav Nadapana; Yedija Bagaskara; Yilin Lai; Haige Zhao (Journal of Cardiothoracic Surgery)
Abstract Background Dextrocardia is a rare cardiac malposition where the heart’s normal orientation is reversed and is most commonly associated with situs inversus totalis (SIT). Such cases are technically challenging when heart surgery is needed, especially re-do surgery. Case presentation A 72-year-old female patient was referred to our hospital with complaints of chest tightness and reduced activity tolerance. The patient had a history of mitral valve replacement (MVR) with a bioprosthesis ten years prior. Chest X-ray showed dextrocardia with SIT in the patient. Structural valve degeneration of the mitral bioprosthesis and moderate tricuspid regurgitation were observed by transthoracic echocardiography. The patient underwent a successful re-do mitral valve replacement under ventricular fibrillation (VF) via a left anterolateral mini-thoracotomy. The recovery of the patient was uneventful. Conclusions Redo MVR under VF without aortic cross-clamping through a mini-thoracotomy can be safely and effectively carried out in patients with SIT.